2022
DOI: 10.3934/neuroscience.2022005
|View full text |Cite
|
Sign up to set email alerts
|

Long lasting effect of acute restraint stress on behavior and brain anti-oxidative status

Abstract: <abstract> <p>Exposure to certain acute stressors results in an immediate behavioral and physiological response to these situations during a significant period of days. The goal of the current study is to evaluate the long-lasting effect of single exposure of restraint stress among mice after 0 h, 24 h, 48 h and 72 h. Five groups of mice are under experiment: a control group and four groups exposed to one session of restraint stress. All these groups have been studied for behavioral tests in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…The results revealed that mice subjected to Evans-blue-fed restraint stress treatment exhibited anxiety-related behavior, providing evidence of psychological stress’s contribution to this model ( Figure 1 ). These findings are consistent with numerous previous reports that have identified psychological stress as one of the major factors associated with restraint stress animal models [ 6 , 7 , 8 , 16 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Additionally, as psychological-stress-induced immunosuppression is rarely discussed, this model is suitable to address this question.…”
Section: Resultssupporting
confidence: 93%
“…The results revealed that mice subjected to Evans-blue-fed restraint stress treatment exhibited anxiety-related behavior, providing evidence of psychological stress’s contribution to this model ( Figure 1 ). These findings are consistent with numerous previous reports that have identified psychological stress as one of the major factors associated with restraint stress animal models [ 6 , 7 , 8 , 16 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Additionally, as psychological-stress-induced immunosuppression is rarely discussed, this model is suitable to address this question.…”
Section: Resultssupporting
confidence: 93%
“…Our findings showed that the SIS rats displayed poor recovery of learning behavior in the passive avoidance test compared to the SG rats, which was improved by the antioxidant and anti-inflammatory effects of AC treatment. This result is consistent with a previous study that evaluated the potential of AC [ 68 ].…”
Section: Discussionsupporting
confidence: 94%
“…Self-grooming is an important behavior observed in rodents, primarily to maintain body hygiene, thermoregulation, chemocommunication, and stress reduction [ 67 ]. Chronic restraint stress, which has been well documented [ 68 ], is known to disrupt emotional activities, aligning with the findings of our study that emotional activities are significantly reduced in SIS rats compared to SG rats. In this study, AC treatment enhanced emotional activities (grooming and rearing), which were suppressed by SIS, consistent with Rauniar et al .…”
Section: Discussionsupporting
confidence: 92%
“…In the acute stress conditions activity of LC norepinephrine neurons participate in arousal reaction, together with action of elevated levels of hormones [5]. Excessive increased activity of brainstem neurons causes oxidative stress which could be a factor for further development of different psychopathologies [6].…”
Section: Introductionmentioning
confidence: 99%